Pengembangan Novelet Berbahasa Jawa Bertema Sejarah Semarang untuk Pembelajaran Sastra Jawa SMA/Sederajat - ZUSTIYANTORO, DHONI; Widodo, Widodo; Safitri, Rani Nur; Wahyuni, Mita (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
The existence of Javanese novels in Javanese literature learning has a standard thickness of novels (more than 100 pages) with various themes. Not all novels that have been published can be used as study material in literature learning. Literary works that can be used as teaching material with the theme of Semarang history. There are various values ​​of life that can be learned, such as religion and tolerance, openness, and discipline, and hard work. There are two main objectives of the research, namely (1) the characteristics of the needs of teachers and students and (2) the draft novelet in Javanese with the theme of Semarang history. This development research was carried out with a research and development (R&D) design developed by Borg and Gall (2003) and modified into two stages, namely (1) preliminary studies and (2) draft development. The characteristics of the needs of teachers and students are seen from the four aspects of book feasibility, namely material, language, presentation, and graphics. The novelet draft consists of the beginning, the content, and the end. The initial section consists of the title page, the publication page, the table of contents page, and the foreword page. The contents of the novelet draft consisted of four short novels with historical themes in the city of Semarang, such as Ki Ageng Pandanaran, Admiral Cheng Ho, the legend of Gua Kreo, and the Five Days Battle in Semarang. The final section contains the author's biography.